2021
DOI: 10.15448/1980-8623.2021.2.36084
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors associated with adolescent sexual behavior

Abstract: Sexually transmitted infections are increasing in Brazilian adolescents and youth. The aim of this study was to investigate the association of self-esteem, self-efficacy, and other psychosocial variables with condom use behavior and sexual debut in a sample of adolescents from Santa Maria-RS. Data was collected with 452 adolescents (57% girls), mean age of 15.9 years (SD = 1.4), using the Brazilian Youth Questionnaire – Phase II. Condom use behavior was not associated with self-esteem or self-efficacy in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Except for sexual behavior, behavioral habits were similar between students on both campuses. Differences in sexual behavior between students, specifically regarding greater reports of sexual intercourse among urban campus students, may be related to aspects such as self-efficacy, religiosity, and family support, which are the variables associated with the onset of sexual life among adolescents [ 61 , 62 ]. Sexual initiation, which usually occurs during adolescence, can be an indicator of risk for sexual abuse, early pregnancy, and sexually transmitted diseases [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Except for sexual behavior, behavioral habits were similar between students on both campuses. Differences in sexual behavior between students, specifically regarding greater reports of sexual intercourse among urban campus students, may be related to aspects such as self-efficacy, religiosity, and family support, which are the variables associated with the onset of sexual life among adolescents [ 61 , 62 ]. Sexual initiation, which usually occurs during adolescence, can be an indicator of risk for sexual abuse, early pregnancy, and sexually transmitted diseases [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents, according to this notion, are at the pinnacle of their growth. The manner in which adolescents are educated and exposed to sexuality will have a big impact on whether or not they establish a healthy sexual identity [24]. This is due to the physical and emotional features of maturity emerging in teens, as well as the social, intellectual, and spiritual beginnings of the early years being sharpened, tested, and sculpted for the future during this time.…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…Positive self-esteem is associated with the development of a range of mental disorders and social problems, including depression, anxiety, violence, high-risk behaviors, and substance use. Self-esteem is crucial in risk-taking behavior; this may also apply to SRB, although the data is currently ambiguous [24]. Several studies have found a relationship between poor self-esteem and sexual risk behavior in adolescence (e.g., early sexual intercourse, inconsistent contraceptive and condom usage), as well as the repercussions of the latter, such as undesired pregnancy and STIs [32,33].…”
Section: Psychosocial Factorsmentioning
confidence: 99%